DIATESIS DALAM KATEGORI GRAMATIKAL VERBA BAHASA JEPANG - Lina Rosliana (Universitas Diponegoro, 2014)
Grammatical categories is an important part of Japanese study to understand the structure of a particular grammar. Grammatical categories in Japanese linguistics is divided into two; grammatical categories of nouns and verbs grammatical categories. Diathesis included into the grammatical categories of verbs which mainly examines the passive and causative form. The core of the study diathesis are different points of view in understanding a situation in a proposition.